Factors Influencing Air Cargo Business: Business Plan and Strategy, Professional Human Resources, and Airlines’ Performance - Rifqi Raza Bunahri (DINASTI RESEARCH, 2023)
The air cargo business has facilitated international trade and the global economy. It plays an important role due to its characteristics, such as long-distance capability, short transport times, low network density, and comparatively low transport capacities. This article then tried to explain and analyze some prominent factors that are influencing the air cargo business. During the research process, the author used a qualitative method by focusing on the literature review design. The result of this article showed that three prominent factors have a significant influence on the air cargo business. First, business plan and strategy by creating an integrated and consolidated plan to achieve competitive advantage. Second, professional human resources or actors who have a crucial role in air cargo operations, such as the shipper, freight forwarder of integrator, customs agent, and ground handling agent. Third, airlines’ performance can be found in product and service quality improvement. Furthermore, other factors also have an influence, namely airport management, economic factors, government policies, the air cargo market, technology advancement, and environmental issues.